Foundation and earth - Asimov, Isaac, 1920- (Garden City, N.Y. : Doubleday, 1986)
Rejecting past technology and mentalics for future galactic development, Golan Trevise pursues the secrets of earth as an alternative to a psychic confederation.
Keywords: Science fiction